Zastosowanie standardowego modelu tobitowego w prognozowaniu opóźnienia w spłacie kredytu - Marzec, Jerzy (Application of Standard Tobit Model to Forecast of Delay on Paying Off Loans, 2006)
The aim of this study is to present a use of the tobit model to examine how debtors pay off debt consumer loans. A explained variables represents a length of a delay in paying off loan and thus the dependent variable is zero for a significant fraction of the observations. Therefore the use tobit model appeared to be relevant for purposes of this study. We show interesting results of the empirical research using the data from a large Polish commercial bank. In a case of various clients we predict the delay in credit loan payments which depends on eleven explanatory variables such as: sex, age, size and source of client's income, loan amount and period, type and currency of loan, information about using a cheque deposit account and credit or payments (ATM) cards by debtors and the way a loan is given (by an agent or not).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 260-273